Comparison of single trough-based area under the concentration–time curve versus trough concentration for the incidence of vancomycin-associated nephrotoxicity. Issue 7 (July 2022) - Niwa, Takashi; Yasue, Moeka; Harada, Saki; Yamada, Yuto; Otsubo, Manami; Yamada, Michi; Matsuoka, Serika; Yamamoto, Taishi; Mizusaki, Yurika; Suzuki, Akio
Abstract: Introduction: While the revised 2020 consensus guideline recommends the use of area under the concentration–time curve (AUC)-guided vancomycin monitoring, collecting multiple vancomycin serum samples to calculate the AUC may cause clinical complications. The aim of the present retrospective study was to evaluate whether AUC-guided vancomycin monitoring, in which AUC was calculated based on a single trough concentration, is a better predictor of nephrotoxicity than trough-guided monitoring in patients receiving vancomycin therapy. Methods: A single-center, retrospective cohort study was conducted at the 614-bed Gifu University Hospital in Japan. Patients who received intravenous vancomycin for a documented or suspected infection and had their serum vancomycin trough concentration monitored between October 1, 2016 and September 30, 2020 were enrolled in the present study. Results: Multivariate Cox proportional hazard analysis indicated that AUC (>600 μgh/mL) was a significant risk factor for the incidence of acute kidney injury (AKI), while trough concentration (≥15 μg/mL) was not. Moreover, the AUC (>600 μgh/mL) showed higher specificity and similar sensitivity to the trough concentration (≥15 μg/mL). Kaplan-Meier plots of the cumulative incidence of the AKI-free rate in patients indicated that the onset of AKI was significantly longer in patients with AUC ≤600 μgh/mL than in patients with AUC >600 μgh/mL (HR, 16.1; 95% CI, 6.3–41.2; p < 0.001). Conclusion: AUC based on a single trough concentration was a better predictor of nephrotoxicity than trough concentration.